How much do Romanian medical students know about research ethics? A survey - Octavian Andronic; Alexandra Bolocan; Dan Nicolae Păduraru; Daniel Ion; Florentina Musat (European Science Editing, 2022)
Background: Although scientific research in Romania has continued to expand over the past 20 years, it is unclear how prepared the country’s students are to be involved in research and to publish the results of their work.Objectives: To assess Romanian medical students’ level of knowledge about research integrity and research ethics.Methods: A cross-sectional survey of 187 medical students (of which 70% were women) from Carol Davila University of Medicine and Pharmacy, Bucharest, Romania, was performed between September 2017 and June 2018. The survey consisted of self-evaluation with respect to three aspects, namely knowledge of research in general, that of research integrity, and that of publication integrity. The self-evaluation was followed by a set of 17 questions that tested the respondent’s knowledge.Results: On average, the proportion of correct answers was 34% (range, 12%–65%). Whereas those who had assigned low grades to themselves (a score below 5) fared poorly (fewer correct answers) in the test that followed, those who rated themselves highly (a score of 5 or higher) did not fare as well as they were expected to. The majority of respondents (83%) were willing to learn more about research integrity through courses, workshops, training programmes, etc.Conclusion: The respondents showed a low level of knowledge related to both research integrity and current standards of reporting scientific research. This lacuna demonstrates the need to train students at the beginning of their academic life because more and more of them, both undergraduate and postgraduate, are likely to be involved in scientific research.